Inovasi program motekar melalui pembelajaran jarak jauh di masa Pandemi Covid-19 SD Maruyung II - Sopia, Evip (Educenter : Jurnal Ilmiah Pendidikan, 2022)
This paper aims to improve the quality of education in Maruyung II Public Elementary Schools. The Image Strategy has been implemented at Maruyung II Public Elementary Schools in the 2019-2020 academic year. This study uses qualitative data. The data is obtained from the documentation and practice of education service providers at the Maruyung II State Elementary School with the sample in this study including students in grades I to d. VI totalled 343 students. The data is obtained from the documentation and practice of education service providers at the Maruyung II public elementary school. It can be concluded that the Motekar method can increase the number of teachers according to their needs and qualifications. The increasing image of the school is evidenced by the increase in public trust so that many parents send their sons and daughters to school so that the number of students from year to year increases. Facilities and infrastructure have increased, which previously did not exist. What was there became better. With the Motekar Strategy, the principal will become the 1st winner of the outstanding school principal in Tanjungsari District in 2022.